P-glycoprotein expression skews mitochondrial dye measurements in T cells - Sophia P. M. Sok; Jianan Cheng; Klaudia Strucinska; Narcis I. Popescu; Lihua Wu; Qiuqing Ke; William B. Kiosses; David Stanford; Willard M. Freeman; Satoshi Matsuzaki; Tommy L. Lewis; Tommy L. Lewis; et al. (Frontiers in Immunology)
Assays to monitor metabolic parameters of immune cells at a single cell level provide efficient means to study immunometabolism. We show here that staining intensity of mitochondria targeting probes in T cells is dramatically influenced by P-glycoprotein/P-gp expression, a xenobiotic efflux pump that extrudes these fluorescent dyes. Discrepancies between MitoTracker Green FM/MTG signals and multiple dye-independent measurements are seen in CD4 T and CD8 T cell subsets and are corrected by P-gp inhibition (PSC833) during MTG staining. We further investigate invariant Natural Killer T (iNKT) cells, which express the highest level of P-glycoprotein among T cells. Using mtDNA abundance, mitochondrial volume, respiration and proteomics, we establish that iNKT cells have higher mitochondrial content and activity than CD4 T cells, opposite to what MTG signals reveal. A similar phenomenon is also seen in human PBMCs, and with TMRE, a dye indicator of mitochondrial membrane potential. Collectively, these data argue that P-glycoprotein expression is a significant confounding factor when analyzing T cells using mitochondrial specific dyes. Complementary methods are necessary to reliably assess mitochondrial features in T cells.